Daniel Disney papers - Disney, Daniel, active 1767.
Volume (274 pages) of orders, regulations, and accounts of daily activities, appointments, promotions, courts-martial, etc., kept by Disney as lieutenant and adjutant in the 44th Regiment of Foot of the British Army under commanders Edward Braddock and John Campbell during the French and Indian War. Includes detailed orders relating to troop movements between New York and Halifax, Nova Scotia, and a journal relating to the siege (1757) of Fort William Henry by French and Indian forces under Rigaud de Vaudreuil. Other material relating to the siege includes records of interrogation of two French prisoners and a copy of a letter from George Bartman, aide-de-camp to Gen. Daniel Webb, to Lt. Col. George Munro stating Webb's inability to offer assistance.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
British army officer.
Collection material in English.
Keywords: Bartman, George -- Correspondence; Braddock, Edward, -- 1695?-1755.; Loudoun, John Campbell, -- Earl of, -- 1705-1782.; Munro, George -- Correspondence; Vaudreuil, Louis Philippe de Rigaud, -- marquis de, -- 1724-1802.; Webb, Daniel, -- approximately 1700-1773.; Great Britain. -- Army. -- Regiment of Foot, 44th (East Essex); Anglo-French War, 1755-1763.; Fort William Henry (N.Y.); Halifax (N.S.) -- History; New York (State) -- History -- French and Indian War, 1754-1763.; Nova Scotia -- History -- 1713-1763.; United States -- History -- French and Indian War, 1754-1763.; Army officers, British